Genophenotypic Analysis of Pediatric Patients With Acute Recurrent and Chronic Pancreatitis. Issue 9 (October 2016) - Palermo, Joseph J.; Lin, Tom K.; Hornung, Lindsey; Valencia, C. Alexander; Mathur, Abhinav; Jackson, Kimberly; Fei, Lin; Abu-El-Haija, Maisam
Abstract : Objectives: The aim of this study was to determine if comprehensive genetic testing was useful to identify genetic variants that discriminate chronic pancreatitis (CP) from acute recurrent pancreatitis (ARP) in a pediatric population. Methods: We conducted a retrospective review of 50 patients enrolled in our institutional pancreatitis registry between April 2013 and January 2015. Genetic analysis of PRSS1, CFTR, SPINK1, and CTRC classified variants as mutations or variants of unknown clinical significance and the minor allele frequency of variants in our cohort was obtained. Results: Genetic testing was obtained in 16/16 (100%) of CP and 29/34 (85%) of ARP patients. A total of 39 genetic variants were found in 27 (60%) of 45 subjects tested with 5 (11%) subjects having 2 different genes affected. Variant frequency was greatest in patients for CFTR (17/45, 38%) followed by SPINK1 (11/44, 25%), CTRC (2/27, 7%), and PRSS1 (2/44, 4%). CFTR variants were more likely in those with CP compared to ARP (63% and 24%, P = 0.01). Conclusions: This study is the first to find a higher rate of CFTR mutations in CP versus ARP groups using comprehensive genetic testing in a pediatric population.